HOW THE CONTROLLED SYNERGY OF RHIZOSPHERIC MICROORGANISMS CAN IMPROVE EFFICIENCY OF MODERN AGRICULTURE (BACK TO NATURE) - Baranskyi Д. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
One of the main goals of sustainable intensification of agricultural production is to increase the content of organic matter in the soil by increasing the strength and diversity of soil microbiota. The rhizosphere is distinctly different from the soil far from the plant roots by its physical, chemical, and biological properties. The number of microorganisms in the rhizosphere can be ten times higher than the content of them in undeveloped soil. Microbial populations play an important role in the phase processes that ensure stability and productivity of agroecosystems. The role of the soil microbiome in regulating many processes in agroecosystems is insufficiently studied, which limits our ability to predict how the reduced soil biome diversity indirectly affects human welfare through agroecosystem resilience. The use of microorganisms has a great potential for sustainable agriculture, because such innovative methods in plant breeding technologies can replace traditional methods of growing agricultural crops. The soil microbiome is a critically important factor influencing the agroecosystem functioning, because microorganisms act as drivers of the circulation of nutrients, regulating the dynamics of labile organic matter in the soil, carbon deposition in the soil, greenhouse gas emissions, changing the physical structure and water regime of the soil, increasing the amount and efficiency of nutrients absorption by plants, prevent the invasion of pathogenic organisms and reduce the impact of biotic and abiotic stresses on the agricultural plants. The rhizosphere should be considered as a structural and functional unit of the agrosystem. Its vital activity determines realization of the genetic potential of varieties and hybrids, creates conditions for increasing their productivity when the soil activity is stimulated and environmental risks are reduced. The present review emphasizes importance of the soil microbiome diversity in maintaining healthy soils, because only such soils support efficient agricultural production.